410 Effect of relative dietary concentration of zinc amino acid complexes on growth performance and carcass characteristics of finishing beef steers - a nine study pooled analysis. (5th December 2019) - Reinhardt, Christopher; Millican, Allison; Wickersham, Tryon; Larson, Connie; Branine, Mark
Abstract: A nine-study retrospective pooled analysis was conducted to evaluate effects of relative dietary concentration of supplemental Zn provided as an amino acid complex (ZnAA) on growth, feed efficiency, carcass quality and yield in finishing beef steers. Data from nine well-controlled studies conducted at university and commercial feedlot research facilities in AB, IA, KS, OK and TX were evaluated using 249 pens ranging from 6 to 275 steers/pen (Total number=14, 096 animals.; initial BW = 340± 6.2 kg). Dietary ZnAA concentrations were defined where; Level 0 = < 30 mg -1 ·kg -1 ; Level 1 =30 – 59 mg -1 ·kg -1 ; Level 2= 60 – 89 mg -1 ·kg -1 ; Level 3= > 90 mg -1 ·kg -1 . Linear (L), quadratic (Q) and cubic (C) effects of dietary ZnAA level were evaluated with pen as the experimental unit and initial BW as a covariate. Carcass-adjusted growth parameters (ADG and Gain:Feed) and final BW indicated a Q response (P ≤ 0.10) with increasing dietary ZnAA concentration, whereas DM intake was not affected by ZnAA level. Hot carcass weight, dressing percentage and ribeye area quadratically increased (P ≤ 0.03) as dietary ZnAA concentration increased. Measures of relative carcass finish (backfat thickness and calculated YG) indicated a L increase (P ≤ 0.01) towards a greater degree of carcass fat as ZnAA increased. Additionally, a L increase in percentage of carcasses grading USDA Choice with increasing dietary ZnAA concentrations and conversely L reductions in percentages of carcasses in YG 1 and 2 categories; suggested dietary ZnAA concentration impacts carcass composition in finishing beef steers. Total and A + liver abscess incidence was reduced (Q; P ≤ 0.01) with Level 2 having the lowest observed incidence. Results suggest a dietary concentration of 60 mg -1 ·kg -1 DM supplemental ZnAA results in optimal growth performance and carcass traits for finishing beef cattle.